Serum Transaminase in Duchenne Dystrophy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers at Children's Hospital Boston, MA, have shown a linear relationship between serum CPK and serum ALT and AST and a logarithmic relationship between serum enzyme levels and age for boys with Duchenne (n=46) or Becker (n=9) muscular dystrophy (DMD or BMD).